Types of competitiveness of Hungarian regions: agglomeration economies and endogenous regional development - Imre Lengyel (European Regional Science Association (ERSA), 2011)
Nowadays, more and more scholars of regional science are interested in the role of agglomeration economies in the knowledge-based economy. This issue can be dealt with from different points of view: the competitive type of functional or nodal regions and one has to examine the factors influencing regional competitiveness. To improve competitiveness of regions, different economic development programmes must be applied, which means that the improvement of competitiveness requires different strategies based on the different types of regions. In this paper we outline our analytical framework: the pyramid model of regional competitiveness and the UFO-model of cluster-based regional economic development. After introducing, we are going to investigate into the competitiveness of Hungarian microregions (LAU1). Our statistical analysis to underline the classification of microregions by competitiveness types is based on a complex methodology of multi-variable data analysis. For the investigation of agglomeration economies in these different types of microregions we apply the location quotient (LQ) method and Ellison-Glaeser-index of traded sectors. The Local Moran Index (LISA), which can be interpreted as the local index of spatial autocorrelation, is used to calculate the neighbourhood effects of the microregions.
Keywords: 330